Taurine Alleviates Pancreatic β‐Cell Senescence by Inhibition of p53 Pathway - Baomin Wang; Ziyan Wang; Yumei Yang; Melody Yuen Man Ho; Runyue Yang; Huizi Yang; Siyi Liu; Huige Lin; Kenneth King Yip Cheng; Xiaomu Li (Journal of Diabetes)
ABSTRACT Background Pancreatic β‐cells function deteriorates during aging, leading to increased risk of type 2 diabetes. We and others previously demonstrated that p53 activation triggers β‐cell senescence and dysfunction in aging, but how its activity is controlled remains incompletely understood. Metabolites are not only by‐products of metabolic pathways but also function as messengers to regulate various biological pathways. Taurine, a non‐proteinogenic amino acid derived from cysteine, has demonstrated anti‐aging effects in multiple cell types and tissues. Nevertheless, its role in β‐cell senescence remains unclear. Methods Untargeted metabolomic analysis was used to determine differential metabolites in pancreatic islets of mice during aging. In vitro, β‐cell lines MIN6 and INS‐1E were treated with taurine and its transporter inhibitor, followed by measurement of senescence‐related markers. Multiple experimental techniques, such as LC–MS/MS, co‐immunoprecipitation, DARTS analysis, and LiP‐MS, were used to study the mechanistic actions of taurine. Results Untargeted metabolomic analysis showed that taurine and taurocholic acid were significantly upregulated in aged islets. Pretreatment with taurine inhibited naturally aging, chemically induced senescent and inflammatory program, oxidative stress, and defective insulin secretion in pancreatic β‐cells. SLC6A6 transporter was required to mediate exogenous taurine uptake, and inhibition of SLC6A6 abolished the anti‐senescent effects of taurine. Taurine bound with CKDN2AIP and inhibited its interaction with p53, thereby promoting p53 degradation and suppressing the p53‐dependent senescent program. Conclusion Our findings suggest that increasing β‐cell taurine uptake might be a feasible approach to preserve β‐cell function by targeting the p53‐dependent senescent response.